The implementation of inclusion services and social interaction for deaf students at Perwira Bogor city elementary public school - Sukmanasa, Elly; Aulia, Karmilasari; Agustiani , Tini; Herawati , Netty; Darmawan , Agus (Jurnal Fundadikdas (Fundamental Pendidikan Dasar), 2024)
Children with special needs face diverse obstacles in social interaction and communication, yet not all struggle equally in these domains. In response, Indonesia's government has implemented inclusive education initiatives to uphold their rights, as mandated by Law No. 20 of 2003. This study investigates inclusive education provision and social interactions among deaf students, regular peers, and teachers, aiming to evaluate services enhancing social integration for deaf students. Employing qualitative methods with descriptive analysis, the research sheds light on the challenges deaf children encounter, particularly in verbal communication, necessitating reliance on visual cues to compensate for hearing impairments. Perwira Elementary Public School employs specialized activities fostering auditory perception and rhythm communication skills. Crucially, parents are instrumental in supporting their children's verbal communication through everyday language practice, aided by hearing devices and teacher guidance. This research underscores the importance of inclusive education initiatives in facilitating social interaction and communication for children with special needs. It provides insights into effective strategies, such as sensory-focused activities and parental involvement, contributing to the broader discourse on inclusive education and its implications for the well-being and development of children with special needs.